Evaluation of a collaborative care system in primary care in the implementation of ambulatory follow-up in mental health: A study protocol - Manuel Dias Alves; Asmaa Jobic; Natacha Rosso; Manon Abello; Aurélie Autret; Jean Vion-Dury; Raoul Belzeaux; Fabien Korrichi (PLoS ONE, 2026)
Access to secondary psychiatric consultation is often challenging for general practitioners (GPs), potentially resulting in treatment delays or increased reliance on emergency services. The med@psy system is a collaborative care platform that enables GPs to schedule consultation appointments with psychiatrists within 48 hours. This study aims to compare the implementation of outpatient follow-up between two care pathways: attendance at a psychiatric emergency department for a consultation followed by discharge home and psychiatric consultation referred by the patient’s GP via the med@psy collaborative care system. The study consists of two prospective, multicenter, comparative and nonrandomized cohorts. Patients will be teleconsulted at one month and again at three months to assess whether they have received appropriate outpatient follow-up. This is a real-life study involving GPs and psychiatrists within a collaborative care model. The strengths and limitations of this study are discussed below. The results of this study will help gather valuable data on these two care pathways and will serve as a basis for improving and optimizing patient management strategies in outpatient mental health care. Trial registration ClinicalTrials.gov NCT06581874